2020
DOI: 10.1073/pnas.2007406117
|View full text |Cite
|
Sign up to set email alerts
|

Highly infectious prions are not directly neurotoxic

Abstract: Prions are infectious agents which cause rapidly lethal neurodegenerative diseases in humans and animals following long, clinically silent incubation periods. They are composed of multichain assemblies of misfolded cellular prion protein. While it has long been assumed that prions are themselves neurotoxic, recent development of methods to obtain exceptionally pure prions from mouse brain with maintained strain characteristics, and in which defined structures—paired rod-like double helical fibers—can be defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Selective, astrocyte-restrictive targeting of unfolded protein response, which is exuberated in reactive astrocytes, via inhibition of PERK signaling was found to prolong the incubation time to the terminal disease in mice [ 14 ]. Moreover, highly infectious prions lacked direct neurotoxicity, indirectly supporting the hypothesis on a non-cell autonomous mechanism of neurodegeneration [ 17 ]. Together with previous work, the current study argues in support of the non-cell autonomous, astrocyte-driven mechanism behind neurodegeneration.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Selective, astrocyte-restrictive targeting of unfolded protein response, which is exuberated in reactive astrocytes, via inhibition of PERK signaling was found to prolong the incubation time to the terminal disease in mice [ 14 ]. Moreover, highly infectious prions lacked direct neurotoxicity, indirectly supporting the hypothesis on a non-cell autonomous mechanism of neurodegeneration [ 17 ]. Together with previous work, the current study argues in support of the non-cell autonomous, astrocyte-driven mechanism behind neurodegeneration.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, partial depletion of microglia exacerbated the reactive phenotype of astrocytes and accelerated disease progression [ 16 ]. Highly infectious prions purified from animals were not directly neurotoxic, supporting the hypothesis on a non-autonomous mechanism being behind prion neurotoxicity [ 17 ]. Indeed, reactive astrocytes isolated from prion-infected animals exhibited synaptotoxic phenotypes characterized by impairment of neuronal growth, inhibition of dendritic spine development and synapse maturation along with impairment of synapse integrity [ 15 ].…”
Section: Introductionmentioning
confidence: 62%
“…Furthermore, uniform mechanism of PrP Sc toxicity does not elaborate on the question of why brain regions exhibit strikingly different, strain-specific vulnerability to PrP Sc [ 82 , 83 ]. Recent studies demonstrated that highly infectious prions are not directly neurotoxic [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not known whether upon activation, astrocytes acquire neuroprotective or neurotoxic phenotypes. Recent studies illustrated that highly infectious prions are not directly neurotoxic [ 51 ], raising a possibility that mechanisms alternative to the direct toxicity of PrP Sc to neurons exists.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is still controversy about the neurotoxicity of PrP Sc . Benilova et al demonstrated that purified highly infectious prions are not neurotoxic, although the whole brain extracts of prion-infected mice were neurotoxic [ 89 ]. Considering that soluble oligomers of AβP are neurotoxic and AβP fibrils are nontoxic [ 90 ], the involvements of the conformation of PrP and its neurotoxicity might be complex.…”
Section: Toxic Functions Of Prp and Neurometalsmentioning
confidence: 99%